The effect of electromagnetic waves on the human body - Rozimukhamedova Shahodat Bahadir qizi; Yusupkhadjayev Elleonora Narimanovna (Genius Journals, 2023)
Artificial electromagnetic waves are the most common and rapidly growing source of exposure in the modern world, including exposure to several groups of frequencies: extremely low frequencies from power lines, car hybrid batteries, and high-voltage lines (>3 Hz-3 kHz); radio frequencies; microwave frequencies, including millimeter waves (3 kHz-300 GHz) from cell phones towers, base stations, and wireless devices, and intermediate frequencies, so-called "dirty electricity" generated by power cables
Keywords: electromagnetic radiation; non-thermal exposure; health